PENGARUH OPINI AUDIT TAHUN SEBELUMNYA, REPUTASI AUDITOR, UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITASTERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN - Ghea Windy Suksesi; Hexana Sri Lastanti (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2016)
The purpose of this study was to determine the previous year’s audit opinion, auditor reputation, company size, profitability, liquidity, and solvability on the provision of going concernaudit opinion on the companies listed in Indonesian Stock Exchange (IDX) during 2012-2014. The method used is the method of causal association. Data used in the study of seconDARy data obtained from financial report that have been published. Sampling was done by using purposive sampling method by using some CRiteria in determining that the study sample was obtained 249 sample. The method of analysis used in this study is logistic regression. Daa processing was performed with SPSS 20. The result show that the previous year’s audit opinion affect the provision of going concernaudit opinion, but auditor reputation, company size, profitability, liquidity, and solvability does not affect on the provision going concernaudit opinion.